Aspects involved in the sustainability of the comprehensive medication management services (Research, Society and Development, 2021)
Comprehensive Medication Management (CMM) services produce positive clinical, humanistic and economic results in several scenarios, and studies have already elucidated the components necessary for its implementation. Despite this, most initiatives are still unsuccessful in maintaining the long-term provision of the service. Thus, this study aimed to understand the elements that contribute to the consolidation and continuation of the CMM service. The chosen methodology was grounded theory. In the period from May 2019 to February 2020, semi-structured interviews were conducted with eight pharmacists and four managers who experienced the offering of CMM in various scenarios of public and private healthcare in Belo Horizonte and the metropolitan region. Records in the first author's field diaries and document analysis were also used. After systematic data analysis, as recommended by the grounded theory methodology, three determinant categories were identified in the CMM sustainability process. The first one, called “Collaborative care is essential: You can't think of CMM just like the pharmacist and patient dyad”, which addresses the essentiality of professional partnerships to strengthen the service. The second category, “Negotiating the sustainability of the CMM”, evaluates important elements associated with service management. And the third, “Who will pay for the service?”, analyzes the possibilities of financial resources in health systems. The results revealed that the consolidation of CMM services is a strategic process, which requires careful planning that begins with the implementation of the service.